2020
DOI: 10.1186/s12889-020-08669-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and associated factors among adolescents in eastern Uganda: a cross-sectional study

Abstract: Background: Globally adolescents constitute over 16% but in SSA, they make up 23% of the population. While little is known about diets of these adolescents, rapid changes in physiological and social processes undergone require adequate diets. This study aimed to determine dietary diversity and associated factors among adolescents residing in the Iganga-Mayuge HDSS. Methods: As part of the African Research, Implementation Science, and Education (ARISE) Network, we analysed collected data among 598 adolescents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 29 publications
(33 reference statements)
8
30
0
Order By: Relevance
“…For this reason, it is important to support programs providing information about food and its preparation, consumption, and utilization to address food and nutrition challenges within a community [ 9 ]. Similarly, the marital status of the head of the household, namely being divorced, in a consensual union, or separated, has a significant positive effect on the HDDS, and in other studies, similar results have been found [ 45 , 67 ]. The area of cultivated land is an important factor that also contributes to improving the dietary diversity of households, and it is important in terms of food production and food diversity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…For this reason, it is important to support programs providing information about food and its preparation, consumption, and utilization to address food and nutrition challenges within a community [ 9 ]. Similarly, the marital status of the head of the household, namely being divorced, in a consensual union, or separated, has a significant positive effect on the HDDS, and in other studies, similar results have been found [ 45 , 67 ]. The area of cultivated land is an important factor that also contributes to improving the dietary diversity of households, and it is important in terms of food production and food diversity.…”
Section: Discussionsupporting
confidence: 80%
“…Dietary diversity provides information on household access to a variety of foods [ 67 ], and the Household Dietary Diversity Score (HDDS) is intended to reflect a household’s economic ability to access a variety of foods [ 32 ]. In other studies, relationships between the HDDS and the socioeconomic characteristics of the households have been captured, including age, sex, level of education of the head of household, employment status or income, food expenditure, size of agricultural land, training received regarding food preparation and human nutrition, among others [ 9 , 55 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 3 food groups were consumed by at least 50% of adolescents in this study namely, starchy staples, milk and milk products and dark green leafy vegetables. Poor consumption of eggs was observed that is similar to ndings among adolescents in Ethiopia and Uganda respectively 16,17 . Despite being a pastoral community, meat was not commonly consumed with adolescents in Samburu cultural value for animals that were not purposively made available for consumption but sold to earn some income and more animals would be held in the herds as a sign of wealth.…”
Section: Dietary Diversitysupporting
confidence: 81%
“…According to WHO, 1.2 billion adolescence live in the world which constitute 16% of the total population in the world [1], with over 253 million in India [2]. Adolescence is a period transition from childhood to adulthood , in which they undergo various rapid changes from physical appearances to changes in the food habits [3,4] . During this period, especially in the low and middle income countries childbearing age starts, particularly for women, which is one of the most precarious time wherein optimum nutritional status need to be achieved.…”
Section: Introductionmentioning
confidence: 99%